2002
DOI: 10.1111/j.0014-3820.2002.tb00851.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Trade-Offs: Testing Predictions on Response to Selection and Environmental Variation

Abstract: The concept of phenotypic trade-offs is a central element in evolutionary theory. In general, phenotypic models assume a fixed trade-off function, whereas quantitative genetic theory predicts that the trade-off function will change as a result of selection. For a linear trade-off function selection will readily change the intercept but will have to be relatively stronger to change the slope. We test these predictions by examining the trade-off between fecundity and flight capability, as measured by dorso-longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 73 publications
(54 reference statements)
7
84
0
Order By: Relevance
“…Previous theoretical work has shown that tradeoffs between key life-history variables may be weak or nonexistent if resource acquisition is more variable than allocation (23, 24), if resource allocation occurs at an earlier hierarchical level (25)(26)(27)(28), if genetic tradeoffs are not constant and change in different environments (29,30), or if bet hedging is the dominant lifehistory strategy in the population (6). Nonetheless, a lack of evidence for growth/reproduction correlations within a population is frequently attributed to lack of power, superabundant Species, sample sizes, and statistics are as in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous theoretical work has shown that tradeoffs between key life-history variables may be weak or nonexistent if resource acquisition is more variable than allocation (23, 24), if resource allocation occurs at an earlier hierarchical level (25)(26)(27)(28), if genetic tradeoffs are not constant and change in different environments (29,30), or if bet hedging is the dominant lifehistory strategy in the population (6). Nonetheless, a lack of evidence for growth/reproduction correlations within a population is frequently attributed to lack of power, superabundant Species, sample sizes, and statistics are as in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, DeHaan et al (2005) contrast phenotypic tradeoff models unfavorably with quantitative genetic tradeoff (QGT) models based on research on wing dimorphism in crickets (Roff et al 2002;Roff and Gelinas 2003). They argue, "Only if tradeoffs are held to be static and bivariate can the phenotypic model be applied to perennial grain breeding" (20).…”
Section: Sexual Allocationmentioning
confidence: 99%
“…More specifically our model assumes that an increase in dispersal ability is correlated with a decrease in fertility (Zera and Denno, 1997;Tanaka and Suzuki, 1998;Roff, 2002;Roff et al, 2002). For simplicity we will assume two extreme scenarios: (i) either the offspring carry all costs as described above (Eq.…”
Section: Dispersal Costs and Maternal Investmentmentioning
confidence: 99%